UPAYA THAILAND DALAM MENGATASI PROSTITUSI SEBAGAI TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) MELALUI KERJA SAMA INTERNASIONAL - intan nurul; Ola Sagita; Wulan Permatasari; Claudia Tivanny; Herli Antoni (Ilmu Hukum Prima (IHP), 2023)
Thailand is a country located in Southeast Asia. 60% of Thailand's income comes from tourist attractions, but nature tourism is a world concern apart from good tourism. However, Thailand is one of the countries known as a place for prostitution which is common in life, so the Thai government seeks to form organizations that aim to suppress or eradicate prostitution through a form of cooperation in the activities carried out by UNIAP including rehabilitation, identification, legal assistance, health assistance, and reintegration. In addition, Thailand also requested assistance from UNICEF as a form of Thailand's efforts to eradicate prostitution and sexual crimes against children. The purpose of this study is to reveal the phenomenon of prostitution in Thailand seen from the characteristics of prostitution places, characteristics of perpetrators and victims, and the mechanism of prostitution that occurs. to become the guiding principle in the implementation of various fields of public life that can regulate order and justice, especially to reveal the reality that occurs in cases of prostitution in Thailand.